Effect of time-based oven-drying on the nutritional quality of cowpea (Vigna unguiculata) leaves - Mafokoane, Agnes, Masedikoe (My University, 2019)
Innovative methods of preserving the quality of traditionally processed green leafy vegetables are underway in Africa. Improvement of processing and preservation methods of leafy vegetables is another way of overcoming perishability restrictions and guaranteeing continued quality food supply in rural areas. The objectives of this study were: to determine the effect of time-based oven-drying on (1) mineral composition, (2) proximate composition and (3) microbial profiling of cowpea (Vigna unguiculata). Separate experiments were conducted for raw and cooked cowpea leaves with four treatments, viz 0 (sun dried), 24, 48 and 72 hours of oven-drying, arranged in a randomised complete block design with 5 replications. In raw cowpea leaves, relative to control (sun-drying), oven-drying period 48hrs, significantly decreased Potassium (K), Manganese (Mn), and Sodium (Na) content in raw cowpea leaves by 6, 9 and 13%, respectively. Similarly, oven-drying period 72hrs significantly decreased Ca, Fe, Mg, Zn, P and S by 5, 11, 16, 18 and 57%, respectively. In cooked cowpea leaves, relative to control (sun-drying), oven-drying period 24hrs significantly increased Na by 18%. Similarly 48hrs oven-drying periods increased Fe and K by 6 and 8%, respectively. Similarly, oven-drying period 72hrs significantly increased Ca, Mg and Mn by 8, 8 and 3%, respectively. In contrast, oven-drying period 72hrs significantly reduced Zn, P and S by 16, 10 and 39%, respectively. Relative to control (sun-drying), oven-drying period 24hrs significantly increased fat by 46% in raw cowpea leaves, however oven-drying period 72hrs significantly decreased protein, moisture, ash, fibre and carbohydrate by 10, 29, 18, 0.5, and 7% respectively. In contrast, relative to control (sun-drying), 72hrs increased energy by 3%. In cooked cowpea leaves, relative to control (sun-drying), ovendrying period 24hrs significantly increased energy by 1%. In contrast, relative to control (sun-drying) 72hrs oven-drying period decreased energy by 1%. Similarly, oven-drying 72hrs significantly decreased protein, moisture, ash, fat, fibre and carbohydrate by 8, 14, 13, 19, 0.4 and 10% respectively. Relative to control (sun-drying), oven-drying periods 24hrs significantly increased Staphylococcus spp. in raw cowpea leaves by 6%, respectively. Relative to control (sun-drying) 72hrs oven-drying period significantly decreased Shigella spp. by 92%, respectively. In cooked leaves, relative to control (sundrying), 72hrs drying periods decreased both Shigella spp. and Staphylococcus spp. by 99 and 21%, respectively. Total coliforms unit of Salmonella spp, Escherichia coli, Pseudomonas spp, and Bacillus cereus were absent and/or at an undetectable level according to the Tempo Biomerieux system results. In conclusion, cooked leaves retained most essential mineral elements as compared to raw when subjected to 72hrs of ovendrying as there was an improvement in the concentration of Ca, Fe, K, Mg, Mn and Na. However, in both raw and cooked cowpea leaves proximate composition was negatively affected as there was a decrease in protein content. Oven-drying period of 24 hours can be used to minimize the loss of protein. Cooked cowpea leaves subjected to 72hrs of oven-drying had least total coliforms for both Shigella spp and Staphylococcus spp, therefore have potential to serve as an alternative to sun-drying to reduce microorganism causing spoilage in leafy vegetables. Drying raw cowpea leaves under oven-drying periods less than 72 hours should be avoided as it reduces the mineral concentration and increase microbial count of microorganisms responsible for spoilage
Thesis(M.Sc.(Agriculture Horticulture)) -- University of Limpopo, 2019
Keywords: Green leafy vegetables; Food supply; Nutrition; Cowpea; Edible greens; Nutrition